Implementasi Pendapat Imam Syafi’i dan Imam Hanafi Terhadap Tanggung Jawab Kerusakan Barang Gadai di Desa Jogoresan Kecamatan Purwodadi Kabupaten Purworejo - Saifudin, Saifudin; Muhajir, M. Ali; Muhajir, Muhajir (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Pawn is the mandate of the loan recipient, if the collateral is seriously damaged, for example a natural disaster occurs, then both rahin and murtahin are responsible for each other. And the pawned goods are moderately damaged, then Rahin is responsible. And if the pawned goods are lightly damaged, then those who are responsible for it are murtahin.This study raises the issue of how the responsibility for damage to the pawned goods according to Imam Syafi'i and Imam Hanafi, if you look at the opinion of the Syafi'i Ulama who say that the murtahin does not bear the damage, while the Hanafi Ulama says that the murtahin is responsible for the damage to the goods.To get good results from the problems above, the authors use research methods that can be simplified and produce good and accountable research, this research is descriptive analytical, in which the authors analyze and provide clarity about the object being studied about the responsibility for damage to goods. pawn according to Imam Syafi'i and Imam Hanafi. This research is a library research where literature is the data source. As for the result, the pawned goods remain the property of the rahin, and if the goods are damaged, Imam Syafi'i is of the opinion that the murtahin does not bear the damage, it is different if the damage is caused by the negligence of the murtahin, then in this case there is no difference of opinion, all scholars agree that the murtahin is responsible. responsible for the damage, and if the item is damaged either by negligence or not, the Hanafi Imam is of the opinion that the murtahin is the one who bears the risk of the damage.